The Influence of Fine-Scale Grazing Heterogeneity on Dung Beetle Assemblages: What Trait Analysis Teaches Us. Issue 6 (28th September 2021) - Perrin, William; Fontana, Simone; Coq, Sylvain; Berlioz, Laurent; Jay-Robert, Pierre; Moretti, Marco
Abstract: Livestock grazing puts major anthropogenic pressure on biological communities worldwide. Not all species are expected to be affected in the same way, and the impacts will depend on species' traits. Focusing on traits thus helps identify the mechanisms underlying changes in community composition under grazing pressures. We investigated how fine-scale grazing heterogeneity affects the trait composition and diversity of dung beetle assemblages in Western Europe. We sampled dung beetles in habitat patches differing in terms of grazing intensity within rangelands of two distinct biogeographical areas: a Mediterranean lowland steppe and Western alpine meadows. We measured five morphological traits expected to respond to the local-scale filtering pressure exerted by variations in grazing intensity. Using individual-based data, we assessed responses in terms of single-trait mean values in communities and complementary trait diversity indices. We found strong shifts in trait composition and diversity between the habitat patches. In both study areas, variations in habitat conditions are likely to have filtered the local occurrence and abundance of dung beetles by the mean of traits such as body mass (which have several functional implications), as well as traits linked to underground activity. We hypothesize that fine-scale variation in resource availability (i.e., droppings) and disturbance intensity (i.e., trampling) are key drivers of the observed patterns in species assemblages. Trait richness peaks at moderate grazing intensity in both study areas, suggesting that patches with an intermediated level of available resources and soil disturbance enable individuals with a greater range of autecological requirements to coexist.